Evaluating the effect of exchange rate and labor productivity on import penetration of Brazilian manufacturing sectors - Jo\~ao Paulo Martin Faleiros; José Carlos Domingos da Silva; Marcos Yamada Nakaguma (EconomiA, 2016)
In recent years, several economists have argued that the sharp loss of competitiveness of the Brazilian industry was caused by a strong exchange rate appreciation. However, other economists have attributed this loss of competitiveness to the dismal growth of labor productivity in the Brazilian industrial sector. The present paper proposes to estimate the differential impacts of variations in exchange rate and labor productivity on the Brazilian market share of imports measured by the coefficient of import penetration of total demand for manufacturing goods. We start by developing a simple theoretical model to investigate under what conditions the impacts of an exchange rate depreciation and an increase in labor productivity would differ. We test the theoretical implications of the model by means of a GMM panel data analysis focusing on 17 manufacturing sectors in the period between 1996 and 2011. Our results suggest that both variables matter to explain the coefficient of import penetration. Nevertheless, labor productivity has the strongest negative impact on the market share of imported goods, even after controlling for sector fixed-effects. – – Recentemente, alguns economistas têm apontado um perigoso processo que consiste na perda de competitividade da indústria brasileira causada pela forte apreciaç\~ao cambial. No entanto, outros economistas têm relacionado esse processo à fraqueza da produtividade industrial brasileira. Neste contexto, o nosso trabalho avalia as diferenças do impacto da taxa de câmbio e da produtividade do trabalho sobre a participaç\~ao das importaç\~oes medida aqui pelo coeficiente de penetraç\~ao da demanda total por bens importados decomposta em setores industriais. Além disso, desenvolvemos um modelo teórico para o entendimento e diferenciaç\~ao de tais impactos. Empiricamente, fazemos uso de uma análise de dados em painel (GMM) considerando 17 setores da indústria transformadora no período entre 1996 e 2011. Nossos resultados sugerem que ambas as variáveis s\~ao importantes para explicar o coeficiente de penetraç\~ao das importaç\~oes. No entanto, a produtividade do trabalho tem o maior impacto sobre a participaç\~ao das importaç\~oes, mesmo quando a avaliaç\~ao é feita em termos de grupos setoriais.
Keywords: 330; Industrial sector; Imports; Exchange rate; Labor productivity; Setor industrial; Importaç\~oes; Taxa de câmbio; Produtividade do trabalho